2017
DOI: 10.1177/0333102417740563
|View full text |Cite
|
Sign up to set email alerts
|

Human mast cells release the migraine-inducing factor pituitary adenylate cyclase-activating polypeptide (PACAP)

Abstract: Background Many patients with migraines suffer from allergies and vice versa, suggesting a relationship between biological mechanisms of allergy and migraine. It was proposed many years ago that mast cells may be involved in the pathophysiology of migraines. We set out to investigate the relationship between mast cell activation and known neurogenic peptides related to migraine. Methods Cultured human mast cells were assayed for the presence of neuropeptides and their receptors at the RNA and protein level. Im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…Unlike infusion of CGRP, PACAP38 infusion correlates not only with a migraine-like headache but also with long-lasting flushing, which has been suggested to be mediated via degranulation of mast cells (Schytz et al, 2009;Seeliger et al, 2010;Bhatt et al, 2014). In vitro evidence supports PACAP38 secretion by activated human mast cells and potentiation of mast cell degranulation (Okragly et al, 2018). Furthermore, using a rodent closed-cranial window model, Bhatt et al (2014) and Jansen-Olesen and Hougaard Pedersen (2018) have shown that PACAP38-mediated, but not CGRPmediated, vasodilation of the middle meningeal artery is mast cell-dependent.…”
Section: Discussionmentioning
confidence: 98%
“…Unlike infusion of CGRP, PACAP38 infusion correlates not only with a migraine-like headache but also with long-lasting flushing, which has been suggested to be mediated via degranulation of mast cells (Schytz et al, 2009;Seeliger et al, 2010;Bhatt et al, 2014). In vitro evidence supports PACAP38 secretion by activated human mast cells and potentiation of mast cell degranulation (Okragly et al, 2018). Furthermore, using a rodent closed-cranial window model, Bhatt et al (2014) and Jansen-Olesen and Hougaard Pedersen (2018) have shown that PACAP38-mediated, but not CGRPmediated, vasodilation of the middle meningeal artery is mast cell-dependent.…”
Section: Discussionmentioning
confidence: 98%
“…The implication of mast cells has been proposed in the pathway activated by PACAP to elicit pain. Mast cells may release PACAP [59], and PACAP, via a hitherto uncharacterized receptor, degranulates mast cells [60]. The present model could be used to further explore local mechanisms that, activated by PACAP and implicating mast cells, result in pain responses.…”
Section: Discussionmentioning
confidence: 99%
“…MC reside in the dura and have been hypothesized to release their pro-inflammatory contents following activation by neuropeptides released from nearby sensory nerve endings, thereby generating neurogenic inflammation (Levy, 2009 ). A recent study revealed that cultured human MCs do not express receptors for either calcitonin gene-related peptide (CGRP) or pituitary adenylate cyclase-activating polypeptide (PACAP), the two neuropeptides most commonly associated with migraine, but rather express and release PACAP upon activation (Okragly et al, 2017 ). Animal models of migraine have investigated the role of MCs more thoroughly and shown that application of MC mediators can sensitize dural afferents and evoke migraine-like behaviors (Yan et al, 2013 ).…”
Section: The Hypothalamic-pituitary-adrenal (Hpa) Axismentioning
confidence: 99%